Self-expandable metal stents as a new treatment option for perforated duodenal ulcer - Bergström, M.; Vázquez, J. A. Arroyo; Park, P.-O. (Endoscopy, 2013)
Primary stenting and drainage has been shown to be an effective and safe way to treat esophageal perforations and anastomotic leaks after gastric bypass surgery. We present a case series of eight patients with perforated duodenal ulcers treated with covered self-expandable metal stents (SEMS). The first two patients received their stents because of postoperative leakage after initial traditional surgical closure. The following six patients had SEMS placed as primary treatment due to co-morbidities or technical surgical difficulties. Endoscopy and stent treatment in these six patients was performed at a median of 3 days (range, 0 – 7 days) after initial symptoms. Six patients had percutaneous abdominal drainage. Early oral intake, 0 – 7 days after stent placement, was possible. All patients except one recovered without complications and were discharged 9 – 36 days after stent placement. This series indicates that primary treatment with SEMS and drainage might be an alternative to surgery in patients with perforated ulcer disease.